Induction of microRNA‐138 by pro‐inflammatory cytokines causes endothelial cell dysfunction. Issue 6 (31st January 2014) - Sen, Anagha; Most, Patrick; Peppel, Karsten
Abstract : Exposure to pro‐inflammatory cytokines, such as Angiotensin II, endothelin‐1 or TNF leads to endothelial dysfunction, characterized by the reduced production of nitric oxide via endothelial nitric oxide synthase (eNOS). We recently identified the Ca 2+ binding protein S100A1 as an essential factor required for eNOS activity. Here we report that pro‐inflammatory cytokines down‐regulate expression of S100A1 in primary human microvascular endothelial cells (HMVECs) via induction of microRNA‐138 (miR‐138), in a manner that depends on the stabilization of HIF1‐α. We show that loss of S100A1 in ECs reduces stimulus‐induced NO production, which can be prevented by inhibition of miR‐138. Our study suggests that targeting miR‐138 might be beneficial for the treatment of cardiovascular disease. Abstract : Pro‐inflammatory cytokines activate HIF1‐α in endothelial cells. Activation of HIF1‐α induces microRNA‐138 and consequent loss of S100A1. Loss of S100A1 inactivates eNOS to cause EC dysfunction. Inhibition of miR‐138 restores S100A1 expression and reverses EC dysfunction.